Water isotopic variability in Mallorca: a path to understanding past changes in hydroclimate. Issue 1 (19th September 2016) - Dumitru, Oana A.; Forray, Ferenc L.; Fornós, Joan J.; Ersek, Vasile; Onac, Bogdan P.
Abstract: This paper reports the first results on δ 18 O and δ 2 H analysis of precipitations, cave drip waters, and groundwaters from sites in Mallorca (Balearic Islands, western Mediterranean), a key region for paleoclimate studies. Understanding the isotopic variability and the sources of moisture in modern climate systems is required to develop speleothem isotope‐based climate reconstructions. The stable isotopic composition of precipitation was analysed in samples collected between March 2012 and March 2013. The values are in the range reported by GNIP Palma station. Based on these results, the local meteoric water line (LMWL) δ 2 H = 7.9 (±0.3) δ 18 O + 10.8 (±2.5) was derived, with slightly lower slope than Global Meteoric Water Line. The results help tracking two main sources of air masses affecting the study sites: rain events with the highest δ 18 O values (> −5‰) originate over the Mediterranean Sea, whereas the more depleted samples (< −8‰) are sourced in the North Atlantic region. The back trajectory analysis and deuterium excess values, ranging from 0.4 to 18.4‰, further support our findings. To assess the isotopic variation across the island, water samples from eight caves were collected. The δ 18 O values range between −6.9 and −1.6‰. With one exception (Artà), the isotopic composition of waters in caves located along the coast (Drac, Vallgornera, Cala Varques, Tancada, and Son Sant Martí) indicates Mediterranean‐sourced moisture masses. By contrast, the drip water δ 18 O values for inland caves (Campanet, ses Rates Pinyades) or developed under a thick (>50 m) limestone cap (Artà) exhibit more negative values. A well‐homogenized aquifer supplied by rainwaters of both origins is clearly indicated by groundwater δ 18 O values, which show to be within 2.4‰ of the unweighted arithmetic mean of −7.4‰. Although limited, the isotopic data presented here constitute the baseline for future studies using speleothem δ 18 O records for western Mediterranean paleoclimate reconstructions. Copyright © 2016 John Wiley & Sons, Ltd.